Case Report: Malignant peripheral nerve sheath tumor of the kidney with a novel granular cell morphology - Ye, Danli; Yan, Guangning; Cui, Wenzhi; Lai, Xuwen; He, Wenyuan; Lei, Chengyong; Wang, Wei (Frontiers in Oncology, 2025)
Malignant peripheral nerve sheath tumors (MPNSTs) arising from the kidney are rare. The present report describes a renal MPNST of a 33-year-old man exhibiting novel morphological features. Histologically, the tumor was comprised of spindle Schwann cells and granular-like tumor cells. The latter are characterized by large, round-to-polygonal cells with abundant, finely granular eosinophilic cytoplasm, which form variable nodules or are diffusely distributed among the spindle tumor elements. Immunohistochemistry revealed both tumor components expressed CD56, Leu-7, PGP9.5, and Nestin, indicating a neural crest origin. A complete loss of H3K27me3 expression confirmed the diagnosis of MPNST. The patient had no history of neurofibromatosis type 1. The granular cell changes in renal MPNST expand the known morphological spectrum of MPNSTs.